thu gọn
\(P(x)=-x(x+5)-(2x-3)+x^2(3x-2)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(P\left(x\right)-x\left(x+5\right)-\left(2x-3\right)+x^2\left(3x-2\right)\)
\(P\left(x\right)=-x^2-5x-2x+3+3x^3-2x^2\)
\(P\left(x\right)=3x^3+\left(-x^2-2x^2\right)-\left(5x+2x\right)+3\)
\(P\left(x\right)=3x^3-3x^2-7x+3\)
b) \(Q\left(x\right)=2x\left(x+1\right)+3x\left(5-x\right)-7\left(x-5\right)\)
\(Q\left(x\right)=2x^2+2x+15x-3x^2-7x+35\)
\(Q\left(x\right)=-x^2+10x+35\)
a: P(x)=-x^2-5x-2x+3+3x^3-2x^2
=3x^3-3x^2-7x+3
b: Q(x)=2x^2+2x+15x-3x^2-7x+35
=-x^2+10x+35
\(2x\left(x-2\right)+5\left(x+3\right)+3\left(x+1\right).\)
\(=2x^2-4x+5x+15+3x+3=2x^2+4x+18.\)
\(5x^2-2\left(x+1\right)+3x\left(x-2\right)+5.\)
\(=5x^2-2x-2+3x^2-6x+5=8x^2-8x+3.\)
(6x+1)(2x-5)=12x2-30x+2x-5=12x2-28x-5
(2x+5)2-2x(2x+8)=4x2+20x+25-4x2-16x=4x+25
(3x-5)(2x-1)-(2x+3)(3x+7)+30x=6x2-3x-10x+5=6x2-13x+5
(X-1)2-(x+1)(x-1)=x2-2x+1-x2+1=-2x+2
(3x+2)(9x2-6x+4)-(3+x)(x-3)=27x3+8+9-x2=27x3-x2+17
1.
a) \(=x^2-6x+9+3x^2-15x=4x^2-21x+9\)
b) \(=9x^2+12x+4-x^2+9=8x^2+12x+13\)
2.
a) \(\Leftrightarrow x^2+8x+16-x^2+4-5=0\\ \Leftrightarrow8x=-15\\ \Leftrightarrow x=-\dfrac{15}{8}\)
b) \(\Leftrightarrow9x^2-6x+1-8x^2+12x-2x+3-5-x^2=0\\ \Leftrightarrow4x=1\\ \Leftrightarrow x=\dfrac{1}{4}\)
a: =18x^3y^2-12x^3y^3+6x^2y^2
b: (-3x+2)(5x^2-1/3x+4)
=-12x^3+x^2-12x+10x^2-2/3x+8
=-12x^3+11x^2-38/3x+8
c: =x^2-x-2+3x-x^2
=2x-2
d: =4x^2+12x+9-4x^2+25-(x-1)(x^2+12)
=12x+34-x^3-12x+x^2+12
=-x^3+x^2+46
a) \(P_{\left(x\right)}=3x^2+2x^3+2x+5-x^2-x-5\)
\(P_{\left(x\right)}=2x^3+2x^2+x\)
\(Q_{\left(x\right)}=x^3-2x-2+3x-x^2+1\)
\(Q_{\left(x\right)}=x^3-x^2+x-1\)
b) ta có: \(P_{\left(x\right)}+Q_{\left(x\right)}=\left(2x^3+2x^2+x\right)+\left(x^3-x^2+x-1\right)\)
\(=\left(2x^3+x^3\right)+\left(2x^2-x^2\right)+\left(x+x\right)-1\)
\(=3x^3+x^2+2x-1\)
ta có: \(P_{\left(x\right)}-Q_{\left(x\right)}=\left(2x^3+2x^2+x\right)-\left(x^3-x^2+x-1\right)\)
\(=\left(2x^3-x^3\right)+\left(2x^2+x^2\right)+\left(x-x\right)+1\)
\(=x^3+3x^2+1\)
\(M\left(x\right)=2x\left(x-3\right)-5\left(x-2\right)+3x^2\)
\(=2x^2-6x-5x+10+3x^2\)
\(=5x^2-11x+10\)
\(N\left(x\right)=-x\left(x+1\right)-\left(2x-4\right)+x^2\left(2x-3\right)\)
\(=-x^2-x-2x+4+2x^3-3x^2\)
\(=2x^3-4x^2-3x+4\)
\(M\left(x\right)-N\left(x\right)-x^2\left(x+6\right)\)
\(=5x^2-11x+10-\left(2x^3-4x^2-3x+4\right)-x^2\left(x+6\right)\)
\(=5x^2-11x+10-2x^3+4x^2+3x-4-x^3-6x^2\)
\(=-3x^3+3x^2-8x+6\)
=>P(x)=-x2-5x-2x+3+3x3-2x2
=3x3-3x3-7x+3.
à nhầm
=>P(x)=-x2-5x-2x+3+3x3-2x2
=3x3-3x2-7x+3.